Edukasi Pencegahan Pre Eklampsia Dan Determinan Post Partum Blues Untuk Kesehatan Ibu Dan Anak - Liliek Pratiwi; Uus Husni Mahmud; Ito Wardin; Harnanik Nawangsari; Maharnani Tri Puspitasari (Lembaga Pengembangan Kinerja Dosen, 2024)
Introduction: According to the Indonesian Health Profile (2021), preeclampsia or eclampsia, bleeding, and COVID-19 caused the highest number of maternal deaths in 2021. In 2022, the maternal mortality rate in Indonesia reached 183 deaths per 100,000 live births, with preeclampsia as the main cause. One of the most common maternal health problems in Indonesia is preeclampsia, which has a high incidence rate and causes dangerous complications for the mother and baby. Research and prevention efforts continue to be needed to reduce maternal mortality in Indonesia. Apart from disorders during pregnancy, we as academics who continue to be pro-active in community service activities in our field, must also pay attention to post-partum health. The incidence of postpartum blues in Indonesia will reach 50-70% in 2023. According to WHO, around 10% of pregnant women and 13% of new mothers experience mental health disorders, especially depression. Risk factors that increase the possibility of postpartum blues are the mother's young age, lack of support from her husband, and a difficult economic situation. Method: The method used in this activity is lecture and discussion, using power points and leaflets. Target: Women of Childbearing Age (WUS), pregnant women and post partum mothers. Results: After the educational activity, participants asked several questions, such as how to know whether a pregnant woman is experiencing problems, how many times should she have an examination, and what should the family do if the mother seems stressed after giving birth. With the aim of improving the welfare of pregnant women and babies, Family Centered Maternity Care (FCMC) is a midwifery approach that involves the family. This approach provides good social support to pregnant women, which can help them deal with stress and anxiety that may occur during pregnancy, childbirth and the postpartum period. In addition, pregnant women and their families are given the opportunity to actively participate in decision-making regarding health care, so that they can take responsibility for their own health. Conclusion: When Women of Childbearing Age (WUS) have good knowledge, attitudes and behavior, they will produce a generation of healthy and intelligent children. Health workers and the public must pay attention to the four Ts: too young, too old, too much, and too close. Antenatal visits and postpartum visits, which are types of physical examinations during pregnancy, are well carried out in first-level health facilities.